Cancer risk among glass factory workers: an excess of lung cancer?. Issue 12 (December 1990) - Sankila, R; Karjalainen, S; Pukkala, E; Oksanen, H; Hakulinen, T; Teppo, L; Hakama, M
Abstract : A total of 3749 workers employed for at least three months in two Finnish glass factories (cohorts A and B) were followed up for cancer in 1953-86 through the Finnish Cancer Registry. In cohort A (1353 men, 1261 women), 106 primary cancers were diagnosed among men, and their standardised incidence ratio (SIR) for all cancers was 99. Among women the risk was low (65 cases, SIR 64). In cohort B (450 men, 685 women), the relative risk of cancer was close to unity for both men (57 cases) and women (75 cases). The risk of cancer was analysed by primary site, type of work, years since first exposure, and age at diagnosis. The only significantly increased risks were those of lung cancer among men (SIR 130, 95% CI 100-167, cohorts A and B combined), and skin cancer among glass blowers (SIR 625, 95% CI 129-1827). An increased risk of lung, stomach, and colon cancer as well as of brain tumours has been reported in previous studies. It is postulated that the excess risk of lung cancer, detected in this study, can also be accounted for by lifestyle, and not only by possible occupational exposures, because a similar excess risk of lung cancer has been found previously for all industrial workers in Finland. Although the risk of stomach cancer in this study was increased among glass blowers, it was not high in the largest groups of plain glass workers. The risks of tumours of the central nervous system and colon were not increased either.